Smart drug combinations for cervical cancer: dual targeting of Bcl-2 family of proteins and aurora kinases - Yumol, Jacklyn (Am J Cancer Res, 2020)
Human papillomavirus (HPV) is the main causative agent in cervical cancers. Recurrent cervical cancer is refractory to currently available treatments. Clearly there is an urgent unmet need to investigate new therapeutic strategies for both the newly diagnosed and recurrent patient populations. We have previously shown that the presence of HPV oncogenes sensitizes cells to inhibition of aurora kinases (AURKs), which induces mitotic delay eventually leading to apoptotic cell death. In this study, we explored whether a dual approach of combining an AURK inhibitor, MLN8237 (Alisertib), with a range of Bcl-2 family anti-apoptotic protein inhibitors would accelerate cancer cell killing. Enhanced and rapid cervical cancer cell killing was observed when Alisertib was combined with inhibitors of either Bcl-2 (Venetoclax), Bcl-XL (A1331852) or Mcl-1 (A1210477) proteins, likely by accelerating apoptosis during mitotic delay due to the loss of functional Bcl-2, Mcl-1, or Bcl-XL. This study presents a promising approach to treating aggressive cervical cancers and may apply to other HPV-related cancers.